Cedrela provenance trial in Puerto Rico and St. Croix: Nursery phase assessment - Whitmore, Jacob L. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Cedrela spp. seeds from eight different provenances were planted in Puerto Rico and St. Croix (Virgin Islands) in August and September 1969. The provenances range from northern Argentina to Mexico and the Antilles. The purpose of the study is to test the adaptability of each provenance under field conditions in Puerto Rico and St. Croix. This report corresponds to the nursery stage.